PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN PROSES BELAJAR IPAS SISWA KELAS V UPTD SD NEGERI 81 PAREPARE - Muslimin, Muslimin; Yulia, Yulia; Muh. Naufal Rizqi Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is the low learning outcomes of grade V students. The problem in this study is how to apply the Project Based Learning (PjBL) learning model to improve the learning process of IPAS class V UPTD SD Negeri 81 Parepare students. This research is a class action research (PTK) which aims to determine the process and results of applying the Project Based Learning (PjBL) learning model for class V UPTD SD Negeri 81 Parepare students on the material of the respiratory system in humans. The approach used in the research is a qualitative approach. The data collection techniques used were observation, tests, and documentation. The research subjects were class teachers and students totaling 14 people consisting of 7 girls and 7 boys. The research was conducted in two cycles. In cycle I, the results of research on the learning process were in the sufficient qualification (C) and the percentage of completeness of the learning test results was 64.28%. In cycle II the research results on the learning process increased to good qualifications (B) and the percentage of completeness of the learning test results was 85.71%. The conclusion of this study is the application of the learning model.